2021
DOI: 10.3390/ijerph18094512
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Development of Young Children Who Witnessed Their Parent’s Arrest Prior to Parental Jail Incarceration

Abstract: Most U.S. incarceration occurs in jails, with more than 10 million annual admissions, and most individuals in jail are parents of minor children. In this short-term longitudinal study, we examined the health and development of young children who did or did not witness their parent’s arrest prior to parental jail incarceration. 228 individuals in 76 triads (incarcerated parents, children, at-home caregivers) were enrolled from four jails in two states. Jailed parents and caregivers reported on whether the child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 76 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…Dallaire & Wilson ( 2010 ) found that witnessing parental arrest was associated with poorer emotional regulation skills, lower receptive vocabulary scores, and increased anxious and depressed behaviors for children compared to children with incarcerated parents who did not witness their parents being arrested. In another study on this topic, Poehlmann-Tynan and colleagues ( 2021 ) found that witnessing parental arrests and experiences of stress related to this incident predicted missed developmental milestones, poorer academic skills, and physical health concerns. Most recently, Muentner and colleagues ( 2021 ) found that children who witnessed their father’s arrest experienced higher levels of stress hormones along with “blunted” physiological stress levels.…”
Section: Witnessing the Arrest Of A Parentmentioning
confidence: 99%
See 2 more Smart Citations
“…Dallaire & Wilson ( 2010 ) found that witnessing parental arrest was associated with poorer emotional regulation skills, lower receptive vocabulary scores, and increased anxious and depressed behaviors for children compared to children with incarcerated parents who did not witness their parents being arrested. In another study on this topic, Poehlmann-Tynan and colleagues ( 2021 ) found that witnessing parental arrests and experiences of stress related to this incident predicted missed developmental milestones, poorer academic skills, and physical health concerns. Most recently, Muentner and colleagues ( 2021 ) found that children who witnessed their father’s arrest experienced higher levels of stress hormones along with “blunted” physiological stress levels.…”
Section: Witnessing the Arrest Of A Parentmentioning
confidence: 99%
“…Notably, much of the recent literature in this area specifically examines populations up to age eight (e.g., Muentner et al, 2021 ; Poehlmann-Tynan et al, 2021 ), with little examination of how effects might vary as children age. This is particularly important in the context of prior literature on development for children with incarcerated parents, which suggests that risks and impacts of incarceration affect children differently beginning at approximately age eight, at which point emotional difficulties and attention concerns may transition to externalizing behaviors and difficulty in school (e.g., Poehlmann-Tynan & Turney 2020 ).…”
Section: Witnessing the Arrest Of A Parentmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence also suggests that remote forms of contact offer viable alternatives to increasing positive parent–child connections (Murdoch & King, 2020). Visits can also alleviate negative feelings (e.g., guilt, rejection) surrounding ambiguous loss and memories of a parent's arrest (Arditti, 2016; Poehlmann-Tynan et al, 2021). Moreover, because social support and increased interaction with children can reduce parenting stress and recidivism, visiting has indirect effects on the well-being of children and the intergenerational cycle of incarceration (Arditti, 2016).…”
Section: Public Health Significancementioning
confidence: 99%
“…Parents have an essential role in determining the success of a children's development and are very influential on the psychological condition of the child ( Lacey et al, 2020). The absence of parents physically and emotionally will have very significant negative consequences, both in terms of mental health and family dysfunction (Hall et al, 2021;Lacey et al, 2022;Rampersaud et al, 2022), one of which is caused by parental arrest (Metcalfe et al, 2022;Noel & Hoeben, 2022;Poehlmann-Tynan et al, 2021) which is felt directly by the child. According to Kusnandar in Databoks (2022), which reported news from the Directorate General of Corrections of the Ministry of Law and Human Rights of the Republic of Indonesia, in 2022, there were 227,431 inmates in prisons and 48,741 detainees in detention centers.…”
Section: Introductionmentioning
confidence: 99%